Penerapan Pijat Bayi terhadap Penurunan Kadar Bilirubin pada Bayi Hiperbilirubinemia : Studi Kasus - Reno Cahyo; Citra Setyo Dwi Andhini; Endah Sari Purbaningsih (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Hyperbilirubinemia is a common condition in newborns characterized by yellow discoloration of the skin and sclera due to elevated serum bilirubin levels. If untreated, severe hyperbilirubinemia can lead to kernicterus and permanent brain damage. Phototherapy as the main treatment has limitations such as dehydration and skin rashes, necessitating complementary therapies such as infant massage. This study aimed to identify the application of infant massage in reducing bilirubin levels in an infant with hyperbilirubinemia. A descriptive case study method was applied to 1 male infant aged 2 days with total serum bilirubin of 9.87 mg/dL undergoing phototherapy at Dahlia Room, Kardinah Hospital, Tegal. Infant massage was performed for 10-15 minutes once daily for 4 consecutive days using pure coconut oil with moderate pressure. Bilirubin levels were measured daily using a Transcutaneous Bilirubinometer JM-105. Results showed a progressive decrease in bilirubin levels from 9.87 mg/dL to 5.20 mg/dL (total reduction of 4.67 mg/dL). Bowel movement frequency increased from 2 to 4-5 times/day, sleep quality improved from restless to restful, body temperature remained stable within normal range, and infant comfort improved. The combination of infant massage and phototherapy demonstrated synergistic effects in accelerating bilirubin excretion through enhanced intestinal peristalsis and disrupting enterohepatic circulation. Infant massage is effective, safe, and low-cost as a complementary therapy for hyperbilirubinemia and can be performed by trained healthcare providers or parents after proper education. This study provides daily clinical descriptions of changes in bilirubin levels, defecation frequency, sleep quality, and infant comfort during the implementation of baby field massage combined with phototherapy.